Curb children's social media usage - Fu, Nicole Chew Xiang *; Leow, Serena Wai Yee * (Star Media Group Berhad, 2024)
In Malaysia, it is common to see parents relying on smartphones to pacify toddlers, particularly during meal times at restaurants. As researchers in the field and mothers of toddlers, we are writing this letter out of concern for our young susceptible to physical harm or legal consequences.